Biology and Management of American Black Nightshade (Solanum americanum P. Mill.) in Tomato, Pepper, Cucurbit, and Strawberry - Nathan S. Boyd; Shawn Steed; Chris Marble; Andrew W. MacRae (EDIS)
This revised 3-page fact sheet describes the biology and management of American black nightshade, explaining how to control for it in tomato and pepper, cucurbits, and strawberry. Written by Nathan S. Boyd, Shawn Steed, Chris Marble, and Andrew MacRae, and published by the Horticultural Sciences Department, October 2016.